2020
DOI: 10.1111/bcpt.13501
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk assessment model of contrast‐induced nephropathy after percutaneous coronary intervention in patients with diabetes

Abstract: Contrast agent, one of the most commonly used drugs in interventional radiology, is mainly used for visualizing blood flow and body cavities. 1 Contrast-induced acute injury is one of the main causes of acute renal failure during hospitalization, and it is a serious complication of coronary angiography (CAG) and percutaneous coronary intervention (PCI). 2 Contrast-induced nephropathy (CIN) is a serious complication during the procedure of CAG and PCI. 3,4 Previous research has shown that CIN is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Moreover, the worse outcomes of DM patients with ACS could be mediated by the increased risk for AKI hence further emphasizing the great importance of preventive measures for AKI in this group of patients. The independent predictors of AKI in the current study are overall consistent with previously reported risk scores, with the most prominent parameters being CKD, older age and CHF [10,12,28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the worse outcomes of DM patients with ACS could be mediated by the increased risk for AKI hence further emphasizing the great importance of preventive measures for AKI in this group of patients. The independent predictors of AKI in the current study are overall consistent with previously reported risk scores, with the most prominent parameters being CKD, older age and CHF [10,12,28].…”
Section: Discussionsupporting
confidence: 89%
“…Acute kidney injury (AKI) is a common complication in patients presenting with acute coronary syndrome (ACS), particularly following percutaneous coronary intervention (PCI) [5][6][7][8][9]. Furthermore, when AKI occurs in patients with ACS, it is associated with significantly worse short-and long-term outcomes that include increased risk for renal replacement therapy, prolonged hospitalization, greater mortality and economic burden [5][6][7][8][9][10]. Patients with DM are considered to be at increased risk for AKI in the setting of ACS and PCI [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease of LVEF indicated the loss of contractility due to acute ischemia or myocardial necrosis [ 21 , 22 ]. Several studies have indicated that worsened LVEF was a predictor of CI-AKI [ 23 26 ]. In accordance with the previous study [ 23 , 27 , 28 ], our study demonstrated that the age and basal creatinine were independently correlated with CI-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that worsened LVEF was a predictor of CI-AKI [ 23 26 ]. In accordance with the previous study [ 23 , 27 , 28 ], our study demonstrated that the age and basal creatinine were independently correlated with CI-AKI. Cinar T et al also indicated that the age, creatinine and ejection fraction score correlated with ST-elevation myocardial infarction-related cardiogenic shock [ 29 ].…”
Section: Discussionmentioning
confidence: 99%